2023
DOI: 10.3390/polym15102367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of In-Process Heat Treatment on the Mechanical Properties of 3D Printed Thermoplastic Polymer PLA

Abstract: The scientific literature regarding additive manufacturing, mainly the material extrusion method, suggests that the mechanical characteristics of the parts obtained by this technology depend on a number of the input factors specific to the printing process, such as printing temperature, printing trajectory, layer height, etc., and also on the post-process operations for parts, which, unfortunately, requires supplementary setups, equipment, and multiple steps that raise the overall costs. Therefore, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, the mechanical properties remain steady starting from the extrusion temperature of 185 • C. Additionally, it was observed that the print speed and the tested infill patterns had a negligible effect on the mechanical properties. However, the nozzle diameter has an effect on the mechanical parameter, as investigated by Tamas , ag et al [23]. They considered only the Cubic infill pattern (grid), and they added contours (covering walls) to the tensile specimens.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical properties remain steady starting from the extrusion temperature of 185 • C. Additionally, it was observed that the print speed and the tested infill patterns had a negligible effect on the mechanical properties. However, the nozzle diameter has an effect on the mechanical parameter, as investigated by Tamas , ag et al [23]. They considered only the Cubic infill pattern (grid), and they added contours (covering walls) to the tensile specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study examined the effects of in-process annealing by manipulating printing direction, layer thickness, and temperature. The results indicate that heat treatment positively impacts tensile strength, while nozzle diameter and printing direction affect hardness [ 12 ]. The findings suggest the viability of in-process treatments for enhancing manufacturing processes, potentially leading to cost-effective and sustainable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Taguchi analysis, it was highlighted that orientation angle and shell thickness notably impact ultimate tensile strength and moderately influence dimensional accuracy, with a focus on achieving optimal manufacturing outcomes. Similarly, in [ 16 ], the ANOVA analysis emphasized the nozzle diameter as the significant factor for a PLA 3D-printed part’s hardness, while for the tensile strength, the significant factor was identified to be the printing direction.…”
Section: Introductionmentioning
confidence: 99%